The clinical benefit of ruxolitinib across patient subgroups: analysis of a placebo‐controlled, Phase III study in patients with myelofibrosis. (11th March 2013) - Verstovsek, Srdan; Mesa, Ruben A.; Gotlib, Jason; Levy, Richard S.; Gupta, Vikas; DiPersio, John F.; Catalano, John V.; Deininger, Michael; Miller, Carole; Silver, Richard T.; Talpaz, Moshe; Winton, Elliott F.; et al.
Summary Myelofibrosis (MF) patients can present with a wide spectrum of disease characteristics. We analysed the consistency of ruxolitinib efficacy across patient subgroups in the COntrolled MyeloFibrosis Study With ORal JAK Inhibitor Treatment (COMFORT‐I, ) a double‐blind trial, where patients with intermediate‐2 or high‐risk MF were randomized to twice‐daily oral ruxolitinib (n = 155) or placebo (n = 154). Subgroups analysed included MF subtype (primary, post‐polycythaemia vera, post‐essential thrombocythaemia), age (≤65, > 65 years), International Prognostic Scoring System risk group, baseline Eastern Cooperative Oncology Group performance status (0, 1, ≥2), JAK2 V617F mutation (positive, negative), baseline haemoglobin level (≥100, <100 g/l), baseline platelet count (100–200 × 109/l, >200 × 109/l), baseline palpable spleen size (≤10, >10 cm), and baseline quartile of spleen volume and Total Symptom Score (TSS; Q1 = lowest, Q4 = highest). Mean percentage change from baseline to week 24 in spleen volume and TSS were calculated for ruxolitinib and placebo in each subgroup. Overall survival was estimated by Kaplan–Meier method according to original randomization group. In ruxolitinib‐treated patients, reductions in spleen volume and TSS and evidence of improved survival relative to placebo across subgroups were consistent with those seen in the COMFORT‐I population, confirming that ruxolitinib is an effective therapy for the spectrum of MF patients studied in COMFORT‐I.